Grave expectations - Redmond, Heather, 1969- (Redmond, Heather, 1969- Dickens of a crime., 2019)
London, June 1835: In the interest of being a good neighbor, Charles checks in on Miss Haverstock, the elderly spinster who resides in the flat above his. But as the young journalist and his fiancée Kate ascend the stairs, they are assaulted by the unmistakable smell of death. Upon entering the woman<U+2019>s quarters, they find her decomposing corpse propped up, adorned in a faded gown that looks like it could have been her wedding dress, had she been married. A murderer has set the stage. But to what purpose? As news of an escaped convict from Coldbath Fields reaches the couple, Charles reasonably expects the prisoner, Ned Blood, may be responsible. But Kate suspects more personal motives, given the time and effort in dressing the victim. When a local blacksmith is found with cut manacles in his shop and arrested, his distraught wife begs Charles and Kate to help. At the inquest, they are surprised to meet Miss Haverstock<U+2019>s cold and haughty foster daughter, shadowed by her miserably besotted companion. Secrets shrouded by the old woman<U+2019>s past may hold the answers to this web of mystery. But Charles and Kate will have to risk their lives to unveil the truth . . .